Recent Advances and Prospects of Nucleic Acid Therapeutics for Anti-Cancer Therapy - Minhyuk Lee; Minjae Lee; Youngseo Song; Sungjee Kim; Nokyoung Park (Molecules)
Nucleic acid therapeutics are promising alternatives to conventional anti-cancer therapy, such as chemotherapy and radiation therapy. While conventional therapies have limitations, such as high side effects, low specificity, and drug resistance, nucleic acid therapeutics work at the gene level to eliminate the cause of the disease. Nucleic acid therapeutics treat diseases in various forms and using different mechanisms, including plasmid DNA (pDNA), small interfering RNA (siRNA), anti-microRNA (anti-miR), microRNA mimics (miRNA mimic), messenger RNA (mRNA), aptamer, catalytic nucleic acid (CNA), and CRISPR cas9 guide RNA (gRNA). In addition, nucleic acids have many advantages as nanomaterials, such as high biocompatibility, design flexibility, low immunogenicity, small size, relatively low price, and easy functionalization. Nucleic acid therapeutics can have a high therapeutic effect by being used in combination with various nucleic acid nanostructures, inorganic nanoparticles, lipid nanoparticles (LNPs), etc. to overcome low physiological stability and cell internalization efficiency. The field of nucleic acid therapeutics has advanced remarkably in recent decades, and as more and more nucleic acid therapeutics have been approved, they have already demonstrated their potential to treat diseases, including cancer. This review paper introduces the current status and recent advances in nucleic acid therapy for anti-cancer treatment and discusses the tasks and prospects ahead.